In-cell protein landscapes: making the match between theory, simulation and experiment. (February 2021) - Gopan, Gopika; Gruebele, Martin; Rickard, Meredith
Graphical abstract: Abstract : Theory, computation and experiment have matched up for the folding of small proteins in vitro, a difficult feat because folding energy landscapes are fairly smooth and free energy differences between states are small. Smoothness means that protein structure and folding are susceptible to the local environment inside living cells. Theory, computation and experiment are now exploring cellular modulation of energy landscapes. Interesting concepts have emerged, such as co-evolution of protein surfaces with their cellular environment to reduce detrimental interactions. Here we look at very recent work beginning to bring together theory, simulations and experiments in the area of protein landscape modulation, to see what problems might be solved in the near future by combining these approaches.